Physical examination a boon-racoon eyes in a child with neuroblastoma - Bhurat, Rishab; Siri, Machina; Kandasamy, Karpagavalli; Jayaraman, Dhaarani; Scott, Julius Xavier (International Journal of Contemporary Pediatrics, 2024)
Metastatic neuroblastoma often presents with prolonged fever, cytopenias and significant constitutional symptoms, before the abdominal mass is evident clinically. Clues like subcutaneous nodules and racoon eyes can help a clinician to suspect and evaluate appropriately to arrive at a timely diagnosis. We report a 3-year-old girl who had prolonged fever and constitutional symptoms for more than 2 weeks. On evaluation in outpatient visits, child was found to have cytopenia, hence was referred to our center for further management. Clinical examination revealed raccoon eyes with scalp nodules, hepatomegaly and abdominal mass predominantly over left lumbar area crossing over midline. On further investigations including radiological imaging and bone marrow biopsy child was diagnosed with metastatic neuroblastoma. Metastatic neuroblastoma often presents with prolonged fever, cytopenias and significant constitutional symptoms, before the abdominal mass is evident clinically. Clues like subcutaneous nodules and racoon eyes can help a clinician to suspect and evaluate appropriately to arrive at a timely diagnosis.